The Analysis of Illocutionary Acts Used by Sherly Annavita in Indonesia Lawyers Club - Lukluatul Maulidiyah; Didin Nuruddin Hidayat; Alek Alek; Maya Defianty (Journal of Languages and Language Teaching, 2021)
Understanding the illocutionary speech acts performed by prominent speakers in a formal event may bring significant impacts to provide an in-depth explanation of the purposes that the speakers intend to deliver. Sherly Annavita, a young politician and social influencer, was invited to one of Indonesia's prominent TV shows. As an influencer, her statements have often initiated a social movement, which led the researchers to examine how she delivered her thoughts in the public sphere. The present study employed a descriptive qualitative approach to uncovered what illocutionary speech acts performed by the above-mentioned politician and the purpose in each speech act. Data analysis of this study found sixteen (16) illocutionary speech acts performed by Sherly. Assertive Illocutionary Speech Act dominated her statements, followed by Expressive and Directive Illocutionary Speech Acts, respectively. Further, of all speech acts performed, Sherly delivered seven purposes of her statement, namely expressing opinions, notifying, stating arguments, advising, thanking, praising, and criticizing.